Feasibility of Micro-Nanotechnology in Biomedical Applications - Tashtoush, Abdullah M İ (Gebze Teknik Üniversitesi, 2020)
Biomedical devices are multidisciplinary field that have the potential to provide patient with artificial tiny devices and bring them back to their regular life. Organs of the human body are varying in size, structure and function, from neurons in the human brain, which contains around 100 billion neurons,  to nephron in renal system, which in healthy adult has 0.8 to 1.5 million nephrons in each kidney. High-scale of technology as the core of every single device will have a deep impact on fabrication such tiny devices. Therefore, such technology should always be developing and upgrading to meet human needs that is including but not limited to medicine, drugs, food, and sports, etc. Micro/Nanotechnology is capable to perform what no one has ever imagined or even thought possible. Miniaturizing devices using MEMS technology has become essential and strongly required to build such failure organ in human body. Accordingly, a new generation will come to light with new capabilities, new products and new markets. This cannot be done without implementing and adapting higher technology system that will lead to this quality of life.